2016
DOI: 10.1007/s11225-016-9669-9
|View full text |Cite
|
Sign up to set email alerts
|

A Game Semantics for System P

Abstract: In this paper we introduce a game semantics for System P, one of the most studied axiomatic systems for non-monotonic reasoning, conditional logic and belief revision. We prove soundness and completeness of the game semantics with respect to the rules of System P, and show that an inference is valid with respect to the game semantics if and only if it is valid with respect to the standard order semantics of System P. Combining these two results leads to a new completeness proof for System P with respect to its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…We do not know of an analogous result in the literature that works also for infinite convex geometries. However, Theorem 4 in [9] and the completeness results for System P ∞ in [26] suggest that such a representation might also be obtainable for well-founded infinite convex geometries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We do not know of an analogous result in the literature that works also for infinite convex geometries. However, Theorem 4 in [9] and the completeness results for System P ∞ in [26] suggest that such a representation might also be obtainable for well-founded infinite convex geometries.…”
Section: Resultsmentioning
confidence: 99%
“…It follows from Example 7 together with Propositions 11 and 12 in [26] that (Or ∞ ) is a consequence of the axioms in Definition 1.…”
Section: Nonmonotonic Consequence Relationsmentioning
confidence: 93%
See 2 more Smart Citations
“…In [17, 32] it is observed that for developing proof systems for preferential conditional logic it is beneficial to lift the implicit assumption that the family of sets of worlds, relative to which the conditional is evaluated, is closed under intersections. To achieve this they use a simplified semantic clause from [29] that is sensitive to closure under intersections. When one uses the conditional with this semantic clause relative to a family of sets of worlds that is not closed under intersection different formulas turn out to be true than would be true relative to the same family of sets of worlds using the semantic clause from premise semantics.…”
Section: Introductionmentioning
confidence: 99%